Knowledge and Antibiotics Prescription Pattern among Ugandan Oral Health Care Providers: A Cross-sectional Survey - Adriane Kamulegeya; Buwembo William; Charles Mugisha Rwenyonyi (Tabriz University of Medical Sciences, 2011)
Background and aims. Irrational prescription of antibiotics by clinicians might lead to drug resistance. Clinicians do prescribe antibiotics for either prophylactic or therapeutic reasons. The decision of when and what to prescribe leaves room for misuse and therefore it is imperative to continuously monitor knowledge and pattern of prescription. The aim of the present study was to determine the knowledge of antibiotic use and the prescription pattern among dental health care practitioners in Uganda. Materials and methods. A structured and pretested questionnaire was sent to 350 dental health care practitioners by post or physical delivery. All the questionnaires were sent with self-addressed and prepaid postage envelopes to enable respondents to mail back the filled questionnaires. Chi-squared test was used to test for any significant differences between groups of respondents based on qualitative variables. Results. The response rate was 40.3% (n=140). Of these 52.9 % were public health dental officers (PHDOs) and 47.1% were dental surgeons. The males constituted 74.3% of the respondents. There were statistically significant differences between dental surgeons and (PHDOs) in knowledge on prophylactic antibiotic use (P = 0.001) and patient influence on prescription (P = 0.001). Amoxicillin, in combination with metronidazole, was the most common combination of antibiotics used followed by co-trimoxazole with metronidazole. Conclusion. The knowledge of dental health care practitioners in antibiotic use in this study was generally low. A combination of amoxicillin with metronidazole was the most commonly prescribed antibiotics subsequent to different dental procedures.